Research output of Iran over the past two years: Contributions from the European Journal of Translational Myology - Mohsen Khosravi (PAGEPress Publications, 2022)
Over the last two decades, all branches of science and technology have rapidly progressed, including the medical area. In Middle Eastern countries, including Iran, the increased growth of technology and science production has led to this rapid medical progress. Recent evidence has revealed that the increase in the number of scientific papers generated in Iran after the Iraqi imposed war against Iran has been eight times that in six main countries in the Middle East, including Egypt, Turkey, Jordan, Saudi Arabia, Iraq, and Syria. Although Iran's output in sciences has been still small in comparison to developed countries, it has significantly grown in the last decade, which is hoped to continue to increase and improve. The current paper shows a portion of the science production in Iran over the past two years based on papers published in the European Journal of Translational Myology in 2020 and 2021. Although the Issue 32 (1), 2022 in a special section contains several typescripts from Iran, they were not included in our analysis since they have not been yet indexed in the Scopus database. However, our report would encourage researchers of diverse nationalities to take part in research works and author joint papers. Further, this paper can be used to rate the universities and research centers regarding their science output, as well as being beneficial to university students, lecturers, and governments.